A Descriptive Study on Iron Deficiency Anemia in the Adult Population of Khost Province - Sapand, Asmatullah; Muhammad, Dr. Raz; Abdali, Dr. Ashraf (Jour Med Resh and Health Sci, 2023)
Aim of the Study: To know the pattern and frequency of iron deficiency as the cause of anemia in the adult population of Khost Province. Method of the Study: This descriptive study was conducted in patients who came to Abdali Medical Complex during 11th of August 2022 to 11th of August 2023. Total three hundred patients with the age range within more the 18 years old were included in this study who met all the criteria required for this study. In this study patients’ CBC and other related blood tests were checked. Moreover, detailed inquiries were made including chronic diseases, nutritional status, past health conditions, present health problems, Obs/gynecological history of women, family history of anemia were obtained. Results: From all 300 anemic patients, we found 262 (87.3%) patients had iron deficiency and 38 (12.7%) patients had non-iron anemia. Most (183) of the patients (61%) who had less of iron were aged 21 to 45 Years and of whom 179 (97.8%) were females. On basis of serum ferritin level or SFL, we observed the intensity of deficiency of iron and classify into modest, mildest and acute groups. We found 210 (72%) patients had modest iron deficiency anemia, 33 (11%) patients had acute and the remaining 51 (17%) of patients had the mild level of iron deficiency anemia. Significance of the Study: This retrospective research study was conducted to know the pattern and frequency of iron deficiency anemia in adult population so as to provide them with better life support and to maintain of health status of these patients. Likely, our study will add to the data on iron deficiency anemia. Conclusion: According to this study, the prevalence of iron deficiency anemia was more dominant in contrast to other causes of anemia. It was seen that females were more commonly affected by iron deficiency anemia and in whom the pattern of iron deficiency was mostly of the modest type.